Synthesis of Seleno Oxindoles via Iodine-Induced Radical Cyclization of N-Arylacrylamides with Diorganyl Diselenides - Jiang, Hongmei; Shen, Haicheng; Li, Cehua; Jin, Zheng; Shang, Yanxue; Chen, Yufeng; Yi, Min; Du, Juan; Gui, Qing-Wen (Synthesis, 2022)
A mild, radical cascade cyclization of N-arylacrylamides with diselenides for the preparation of oxindoles via iodine oxidation is disclosed that provides an environmentally friendly process for the construction of C–Se bonds. Twenty-five examples of N-arylacrylamide substrates were investigated, and excellent yields were achieved. The tandem cyclization of acrylamide with diphenyl disulfide was also applicable under the same conditions.
Keywords: seleno oxindoles; iodine-induced; radical reaction; C–Se bond; cyclization